Impact index for the characterization of factors affecting milk production in farms of Ciego de ?vila province, Cuba - Mart?nez-Melo, J.; Torres, Verena; Hern?ndez, N.; Jord?, Humberto (Cuban Journal of Agricultural Science, 2013)
In order to characterize the factors affecting milk production in farms of Ciego de ?vila province, a methodology to calculate the impact index for each principal component (PC) was used. It depends on the indicators of higher preponderance in each PC and expresses the highest or lowest effect of each indicator per study case. A total of 372 farms were studied as well as the productive, physical and of efficiency indicators. Five PC explained 72.1 % of the variance. The PC 1, representing the total area of natural grasslands, undesired plants and stocking rate, had higher index in the farms of Majagua municipality and lower in Florencia, while the indicators of the second PC (production and efficiency) showed higher indexes in Florencia. The impact index of PC 3 (feeding basis) indicated higher forage areas in the farms of Majagua and Florencia, while that of PC 4 (reproductive performance) showed a wide variation. The index of PC 5 showed low mortality. It is concluded that considering these factors related with the management, feeding basis, productive and reproductive component and mortality that affect the productive efficiency of the farms is necessary to adjust from the use of a strategy of technological management and of control of sustainability indexes. The impact index contributed to explain the great variability between farms and indicated the higher or lower relative importance of the indicators in the farms of each municipality. Key words: rural dairy systems, multivariate analysis, principal components, efficiency.